2001
DOI: 10.1111/j.1365-2702.2001.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff perceptions of the behaviour of older nursing home residents and decision making on restraint use: a qualitative and interpretative study

Abstract: · This study examined staff perceptions of the behaviour of older nursing home residents and how these perceptions govern their decision making on restraint use.· Data were collected in unstructured interviews with 20 trained and untrained nursing staff from two Swiss nursing homes.· Data analysis was based on Colaizzi's phenomenological method.· Two main themes were extracted from the data: (i) situations in which behaviour is perceived in terms of a problem that needs to be controlled and consequently leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 74 publications
0
52
1
1
Order By: Relevance
“…The present findings also show that the extent of restraint use was not related to the attitudes of the participants toward people with dementia or to their perceptions of restraint use. This is inconsistent with previous findings, which showed a relationship between the decisions of nurses and their interpretation of the behaviour of older people with dementia (Hantikainen 2001) as well as their attitudes toward restraint use (Karlsson et al. 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…The present findings also show that the extent of restraint use was not related to the attitudes of the participants toward people with dementia or to their perceptions of restraint use. This is inconsistent with previous findings, which showed a relationship between the decisions of nurses and their interpretation of the behaviour of older people with dementia (Hantikainen 2001) as well as their attitudes toward restraint use (Karlsson et al. 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…Restraint use is closely related to crucial aspects of patient safety such as preventing falls (M€ ohler & Meyer, 2014) and controlling the behaviours of older adults (Hantikainen & K€ appeli, 2000). While the prevalence of physical restraint use has decreased in Western countries, 78.2% of older adults in South Korea were reportedly restrained by full-side bed rails, with trunk restraints being applied to 31.9% of them (Yoo & Kim, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of research has reported on what constitutes good quality in the care of older people in a community setting, from the point of view of caregivers (Hantikainen, 2001; Puts et al. , 2007), relatives (Jeon, 2004; Janlöv et al.…”
Section: Introductionmentioning
confidence: 99%